Gypsum plaster - John, Vanderley Moacyr (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This article is concerned with the use of gypsum plaster as wall and concrete structure lining. It discusses state-of-art research in this theme, analysing both previous studies and experimental results carried out by the authors. The gypsum used in this study was manufactured according to Brazilian standard specifications on the physical properties of gypsum powder and paste. Regarding the chemical composition, only the SO3 (53.7%) level was below the NBR 13207 specifications (> 55.0%). The fine sand used had the following characteristics: maximum characteristic dimension of 2.4 mm, unitary mass of 1.64 Kg/dm3, specific mass of 2.65Kg/dm3. The experiments followed a 23 factorial design, with two repetitions, considering as factors the water/plaster ratio and the gypsum/aggregate ratio, both in mass. The following parameters were measured for each mixture: texture measured by modified Vicat apparatus, and time to the beginning of the setting, both according to ASTM C 472 (ASTM, 1993). The aggregate level influenced texture, the beginning of the setting, and adherence resistance. The results showed that gypsum plaster is feasible in terms of adherence resistance.